Human Rights and Constitutional Studies: A Comprehensive Review - Rana , Abhishek (Journal of Advanced Research in Public Policy and Administration, 2023)
Human Rights and Constitutional Studies are integral disciplines that underpin the foundations of democratic societies. This comprehensive review explores their historical evolution, key theoretical concepts, contemporary challenges, and intricate interplay. Tracing their roots from ancient civilizations through the Enlightenment era to pivotal moments like the American and French Revolutions, it underscores their enduring significance. Key theoretical concepts are elucidated, encompassing the separation of powers, the rule of law, individual rights, and the adaptability of constitutional amendments. Contemporary challenges come to the fore, including the impact of emerging technologies, the complexities of globalization, the rise of populism and authoritarianism, and the delicate balance between free speech and regulation. The symbiotic relationship between human rights and constitutional studies is scrutinized, focusing on judicial review, international human rights law, and the nexus between constitutionalism and democracy. Case studies from the United States, the European Union, and India provide practical insights into the application of these disciplines. Looking to the future, the study advocates for greater intersectionality and inclusivity, particularly with regards to marginalized communities, as well as heightened attention to environmental rights in the face of climate change. Ultimately, this review underscores the enduring relevance of human rights and constitutional studies in shaping just, equitable, and democratic societies in a rapidly evolving world.